Металлические посудовидные изделия из погребений номадов золотоордынского времени Восточной Европы: проблемы и стереотипы - Потёмкина, Т.М. (Степи Европы в эпоху средневековья, 2012)
The paper considers utilization of a well-known category of grave goods: iron and copper (bronze) tableware-like products with handles in funeral ceremonialism of nomads of the Eastern Europe of the Golden Horde time. A comprehensive analysis of tableware-like products and some characteristics of burials in which they were found enabled the author to come to the conclusion that those objects were made specially for a funeral ceremony. Besides, they possessed semantic bidirectionality, being mediators, i.e. instruments of connection of two opposite worlds. They have no relation to cauldrons and their functions in the funeral ceremony of medieval nomads. It is believed that metal tableware-like products in the Golden Horde nomadic burials present an innovation, whether brought by the Tatar-Mongols during their invasions from the Central Asia, or developed immediately in the "imperial” culture of the Golden Horde.